(untitled) (Journal of the College of Basic Education, 2025)
The current research aims to investigate the effectiveness of an educational program based on the communicative approach in developing reading skills among fifth-grade students.To achieve the research objectives, the researcher formulated the following null hypotheses: (There is no statistically significant difference at a significance level of (0.05) between the mean scores of the experimental group students, who study according( to the educational program, and the control group students, who study using the traditional method, in the reading comprehension skill test)..To achieve the research objectives, the researcher adopted the descriptive and quasi-experimental methods. The research population included fifth-grade students in public primary schools under the Directorate General of Education in Baghdad, Al-Karkh I. The research sample consisted of (70) male and female fifth-grade students from Al-Anwar Mixed Primary School, distributed across two classes. The sample was selected randomly, with(35) students in the experimental group who studied using the educational program based on the communicative approach, and (35) students in the control group who studied using the traditional method. The researcher equalized the groups in the following variables: age, academic achievement, intelligence, prior knowledge, and pre-application of the reading skills test). The researcher also attempted to control several extraneous variables that, according to literature and previous studies, could influence this type of experimental design.To analyze the results, the researcher used the following statistical methods: (Chi-square test, SPSS version (21) educational package, independent and paired sample t-tests, Pearson correlation coefficient, and Spearman-Brown equation). The results showed that the experimental group students outperformed the control group students in all skills within the main null hypotheses